2022
DOI: 10.1021/acs.macromol.2c01087
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Multimer Cyclization Effect during Click Step-Growth Polymerization of AB-Type Macromonomers

Abstract: In this work, by combining size exclusion chromatography (SEC) and liquid chromatography at the critical condition (LCCC) techniques, we have studied the multimer cyclization effect during click step-growth polymerization of AB-type macromonomers. First, by atom transfer radical polymerization (ATRP), we have synthesized a series of alkynyl and azide functional AB-type polystyrene macromonomers with different molar masses, i.e., PS n . Second, via the click step-growth polymerization of a PS n macromonomer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…While Figure evaluates the degradation of a monodisperse network, past theory , and experimental studies have shown that synthesized oligomers are often a polydisperse distribution of chain lengths. As oligomer distribution has been to shown to impact mass loss in traditional polymer networks, this work investigated how dispersity in a thioester oligomer would influence degradation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Figure evaluates the degradation of a monodisperse network, past theory , and experimental studies have shown that synthesized oligomers are often a polydisperse distribution of chain lengths. As oligomer distribution has been to shown to impact mass loss in traditional polymer networks, this work investigated how dispersity in a thioester oligomer would influence degradation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several simplifying assumptions were made to develop this model: (i) the polymers under consideration formed ideal distributions, (ii) the kinetic coefficient for the TTE remained constant throughout degradation and for every thioester in the network, (iii) completely cleaved segments diffused nearly immediately out of the degrading network, and (iv) no further TTE reactions occurred in cleaved segments. These assumptions will not hold for all networks, such as in thick samples, systems with significant oligomer cyclization, 50 systems with pendant chain and cycle formation during polymerization, 49 and systems with nonisothermal exchange reactions that impact the reaction rate constant. 23 Structural Component of the Model.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A turnaround took place in 2002 when the Cu­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) was reported independently by Sharpless et al and Meldal et al , As a typical click reaction, CuAAC could produce sole 1,4-disubstituted 1,2,3-triazoles in excellent yields under mild conditions, which has been developed into a useful polymerization technique, i.e., Cu­(I)-catalyzed azide–alkyne click polymerization (CuAACP) . Thanks to its remarkable click features, CuAACP has been widely used for the preparation of 1,4-regioregular polytriazoles (PTAs) with advanced structures and desired functional properties, which could serve as biomaterials, photoelectric materials, nonlinear optical materials, shape memory materials, self-healing materials, and so on. To avoid the detriment of the residue metallic species to the optoelectronic and bioapplication of the product, metal-free click polymerization (MFCP) of azides and alkynes was also reported by our groups for the preparation of 1,4-regioregular PTAs …”
Section: Introductionmentioning
confidence: 99%